KM in SMEs: a research agenda. (19th March 2009) - Ergazakis, Emmanouil; Ergazakis, Kostas; Flamos, Alexandros; Charalabidis, Yannis
KM is an emerging area, which has gained interest by both enterprises and academics. The effective implementation of a KM strategy is considered as a 'must' and as a precondition of success for contemporary enterprises, as they enter the era of knowledge economy. Big enterprises seem to have fully realised the importance of KM for their operation and the advantages that can offer and in this way, the majority of proposed methodologies, systems and tools (from the part of the research community) is addressed/concerned with big enterprises. This is not the case however for SMEs, the majority of which seem to consider KM as a non-affordable luxury and consequently, the research regarding KM and SMEs has been slow in formulating respective frameworks, methodologies and tools and there are still many pending issues that have to be addressed. However, KM has a lot to offer to SMEs. In this way, this paper attempts to propose a research agenda for the relation of KM and SMEs. The discussion presented in this paper should be of value to researchers and practitioners.